Perancangan Website Profil dan Katalog Digital UMKM Habil Donuts - Asyfa Naswa; Rahmat Fadli Ramadhan; Roif Rozaan Nizora (CV. ITTC INDONESIA, 2026)
This article describes a Project Based Learning (PBL) activity carried out for the Web Design course by students of the Business Administration Study Program, Politeknik Negeri Padang, in collaboration with Habil Donuts, a home-based culinary micro, small, and medium enterprise (MSME) located near Universitas Andalas, Pauh, Padang. Although the store has a strong offline presence and offers eleven varieties of homemade donuts at affordable prices, it did not yet have an integrated digital information channel. The activity was carried out through field observation, an interview with the owner, integration of the existing brand logo, and the development of a responsive single-page business profile and digital catalog website using the no-code platform Site123. The resulting website displays the company profile, an interactive product catalog with price and promotion labels, a WhatsApp ordering button, and an embedded Google Maps location. The website is expected to strengthen branding, support the shift toward digital marketing, and make it easier for customers to access product information in real time.